Minimal Erythema Dose Determination in Holstein Friesian Cattle - Hodnik, Jaka Jakob; Jankovec, Marko; Ježek, Jožica; Krušič, Žiga; Mitterhofer, Stefan; Starič, Jože (Frontiers in Veterinary Science, 2021)
Cattle on pasture are continuously exposed to solar UV radiation, which has been associated with biological effects such as sunburn, photosensitization, squamous cell carcinoma, and cutaneous vitamin D3 production. The minimal erythema dose (MED) required to produce first-degree sunburn (erythema) is poorly researched in cattle. Since cattle are naturally covered with dense hair coats, the MED is influenced by the UV protection offered by the hair. The objective of this study was to determine the MED on intact-hair-covered (MED-H) and shaved white skin (MED-S) of Holstein Friesian cattle. Twenty-one Holstein Friesian cows and heifers were MED tested using a narrowband UV-B LED light (peak irradiance at 292 nm) on 8 hair-covered and 8 shaved areas over white skin previously unexposed to direct sunlight. Erythema was visually assessed after 24 hours. The mean MED-H and MED-S were 5595 J/m2 and 329 J/m2, respectively. Heifers had a higher MED-H compared to cows, 7600 and 4969 J/m2, respectively. The mean UV transmittance of white cattle hair was 6.7%. MED-H was correlated with hair length (Spearman’s rho=0.76). A linear regression model showed that each millimeter of hair coat length increased the MED-H by 316 J/m2. In conclusion, this study provides a MED testing protocol for cattle and reports standardized values of MED for cattle on intact-hair-covered and shaved areas.